Sick Planet: Corporate Food and Medicine - Stan Cox (Pluto Press, 2008)
"Scientist Stan Cox expertly draws out the strong link between Western big business and environmental destruction. This is a shocking account of the huge damage that drug manufacturers and large food corporations are inflicting on the health of people and crops worldwide. Companies discussed include Wal-Mart, GlaxoSmithKline, Tyson Foods and Monsanto. On issues ranging from the poisoning of water supplies in South Asia to natural gas depletion and how it threatens global food supplies, Cox shows how the demand for profits is always put above the public interest."